2002
DOI: 10.1074/jbc.m110235200
|View full text |Cite
|
Sign up to set email alerts
|

Phosphatidylinositol 3-Kinase Controls Human Intestinal Epithelial Cell Differentiation by Promoting Adherens Junction Assembly and p38 MAPK Activation

Abstract: The signaling pathways mediating human intestinal epithelial cell differentiation remain largely undefined. Phosphatidylinositol 3-kinase (PI3K) is an important modulator of extracellular signals, including those elicited by E-cadherin-mediated cell-cell adhesion, which plays an important role in maintenance of the structural and functional integrity of epithelia. In this study, we analyzed the involvement of PI3K in the differentiation of human intestinal epithelial cells. We showed that inhibition of PI3K si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

12
186
0
3

Year Published

2003
2003
2013
2013

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 157 publications
(203 citation statements)
references
References 48 publications
(61 reference statements)
12
186
0
3
Order By: Relevance
“…Several different signaling pathways are required and act in a combinatorial manner to maintain homeostasis in the normal intestinal epithelium. Some of the pathways identified to date include the Wnt pathway (2), the Notch pathway (3), the Hedgehog system (4), members of the transforming growth factor-␤ family including the bone morphogenetic proteins (5), and the phosphatidylinositol 3-kinase pathway (6). The intestine specific gene expression requires the tightly regulated activity of transcription factors, including the well characterized key factors HNF1␣/␤, 2 HNF4␣, GATA factors, ETS, CDX1, and CDX2 (7)(8)(9)(10)(11)(12)(13).…”
mentioning
confidence: 99%
“…Several different signaling pathways are required and act in a combinatorial manner to maintain homeostasis in the normal intestinal epithelium. Some of the pathways identified to date include the Wnt pathway (2), the Notch pathway (3), the Hedgehog system (4), members of the transforming growth factor-␤ family including the bone morphogenetic proteins (5), and the phosphatidylinositol 3-kinase pathway (6). The intestine specific gene expression requires the tightly regulated activity of transcription factors, including the well characterized key factors HNF1␣/␤, 2 HNF4␣, GATA factors, ETS, CDX1, and CDX2 (7)(8)(9)(10)(11)(12)(13).…”
mentioning
confidence: 99%
“…During enterocyte differentiation of CRCs the ERK pathway is switched off, whereas PI 3 K class I and p38 activities are increased and essential for full differentiation. 5,9 It has been suggested that p38a could activate the intestinal-specific homeobox transcription factor CDX2 probably by phosphorylation.…”
mentioning
confidence: 99%
“…During enterocyte differentiation of CRCs the ERK pathway is switched off, whereas PI 3 K class I and p38 activities are increased and essential for full differentiation. 5,9 It has been suggested that p38a could activate the intestinal-specific homeobox transcription factor CDX2 probably by phosphorylation. 10 This mechanism resembles that described for p38a/b in muscle cells, where they phosphorylate the transcription factor MEF2 and the SWI/SNF subunit BAF60 to remodel chromatin and activate tissue-specific transcription.…”
mentioning
confidence: 99%
“…12). E-cadherin-mediated cell-cell contacts also promote intestinal epithelial cell differentiation (21,28) and survival of prostate and breast epithelial cells (13).…”
mentioning
confidence: 99%